Cross-cultural validation and measurement invariance of the learning climate questionnaire in physical education: evidence from Mexico and Spain - Gómez-López, M.; Zamarripa, J.; Pizarro, D.; Ramírez-Nava, R.; Manzano-Sánchez, D. (Frontiers in Psychology, 2026)
IntroductionThis study examined the factorial validity and cross-cultural invariance of the Learning Climate Questionnaire in Physical Education (LCQ-EF) among adolescents from Mexico and Spain.MethodsA total of 1,753 secondary school students (896 Mexican, 857 Spanish) completed the LCQ-EF. Multigroup confirmatory factor analyses tested configural, metric, scalar, and strict invariance, including invariance across genders and two age groups (12–14 and 15–17 years).ResultsThe results indicated excellent internal consistency (α and ω > 0.90) in both samples and supported strict invariance between Mexico and Spain, as well as across genders and two age groups, confirming that the LCQ-EF measures autonomy support equivalently across cultures, gender, and age groups.DiscussionThe findings validate the LCQ-EF as a reliable tool for cross-cultural assessment of the perceived learning climate in Physical Education. The study highlights the universality of autonomy-supportive teaching as posited by Self-Determination Theory and provides a valid instrument to evaluate teacher behaviors that foster motivation and engagement in diverse cultural contexts.